Evaluasi jenis feedstock terhadap produksi biogas dan kualitas bioslurry pada skala rumah tangga di Banyuwangi - Herdianto, Agung; Andhi Krisdhianto; Mohamad Syaifudin Aswan (LPPM Politeknik Aceh Selatan, 2025)
This study evaluates the effect of different feedstock types on biogas production and bioslurry quality at the household scale in Banyuwangi Regency. The assessment focused on biogas byproducts in the form of bioslurry derived from three types of feedstock household organic waste, goat manure, and cow manure. The research employed a completely randomized design (CRD) experimental method, in which each feedstock was fermented in a biodigester for one month, after which the resulting bioslurry was analyzed in the laboratory. The parameters measured included pressure (P), volume (V), daily gas production (ΔV), as well as the quality of bioslurry macronutrients pH, organic carbon, total nitrogen, P₂O₅, K₂O, C/N ratio and tests for pathogenic microbes. The results showed that all three feedstock types have potential as biogas substrates, indicated by positive gas production rates throughout the fermentation period. Cow manure yielded the highest cumulative biogas production potential (ΔV 146.81 liters), followed by household organic waste (ΔV 116.17 liters) and goat manure (ΔV 95.87 liters). In terms of bioslurry quality, cow manure provided relatively higher nutrient content (Ntotal and P₂O₅) compared to goat manure and household organic waste. The household-scale biogas technology applied in Banyuwangi demonstrates significant potential as a renewable energy source. However, its liquid digestate byproduct tends to have low nutrient content and carries biological risks that warrant attention in its utilization. Therefore, post-treatment measures such as composting or further maturation are necessary to ensure bioslurry safety and improve its agronomic value.